Genome-wide analysis of the GRAS gene family in Liriodendron chinense reveals the putative function in abiotic stress and plant development - Weng, Yuhao; Chen, Xinying; Hao, Zhaodong; Lu, Lu; Wu, Xinru; Zhang, Jiaji; Wu, Jingxiang; Shi, Jisen; Chen, Jinhui (Frontiers in Plant Science, 2023)
GRAS genes encode plant-specific transcription factors that play essential roles in plant growth and development. However, the members and the function of the GRAS gene family have not been reported in Liriodendron chinense. L. chinense, a tree species in the Magnolia family that produces excellent timber for daily life and industry. In addition, it is a good relict species for plant evolution research. Therefore, we conducted a genome-wide study of the LcGRAS gene family and identified 49 LcGRAS genes in L. chinense. We found that LcGRAS could be divided into 13 sub-groups, among which there is a unique branch named HAM-t. We carried out RNA sequencing analysis of the somatic embryos from L. chinense and found that LcGRAS genes are mainly expressed after heart-stage embryo development, suggesting that LcGRAS may have a function during somatic embryogenesis. We also investigated whether GRAS genes are responsive to stress by carrying out RNA sequencing analysis, and we found that the genes in the PAT subfamily were activated upon stress treatment, suggesting that these genes may help plants survive stressful environments. We found that PIF was downregulated and COR was upregulated after the transient overexpression of PATs, suggesting that PAT may be upstream regulators of cold stress. Collectively, LcGRAS genes are conserved and play essential roles in plant development and adaptation to abiotic stress.